THE EFFECT OF QUALITY OF WORK LIFE, JOB SATISFACTION, AND PSYCHOLOGICAL EMPOWERMENT ON PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS MEDIATION - Suwanto, Suwanto; Kadarusman (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
This study investigates the impact of work life quality, job satisfaction, and psychological empowerment on performance, with organizational commitment as a mediator. The research uses quantitative methods, including questionnaires distributed to 61 employees at Lippo Karawaci and Lippo Plaza Batu. The data collected will be analyzed using Smart PLS and tests like outer and inner models. The study aims to determine the positive influence of these factors on performance, with organizational commitment as the main variable. The study uses both primary and secondary data sources, with a total of 61 respondents. The results are expected to show a positive influence of these factors on performance, with psychological empowerment acting as a mediator. The study emphasizes the importance of organizational commitment in influencing these factors.